1986
DOI: 10.1177/0013161x86022004002
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Teacher Loyalty to the Principal: Rule Administration and Hierarchical Influence of the Principal

Abstract: The main purpose of this study was to examine the relationships between principal rule administration behavior, hierarchical influence, and teacher loyalty to the principal. An additional intent was to analyze hierarchical influence as a conditioning factor of the principal's rule behavior on teacher loyalty. A significant relationship was found between representative rule behavior of secondary principals and teacher loyalty, and between punishment-centered rule behavior of elementary principals and teacher lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This indicates that teachers are willing to cooperate with their school leaders even though some from the "out-group" have limited relationship with their school leaders. Teachers who show their loyalty to their school headteachers express high commitment and unquestioning faith and trust in their headteachers ( Johnson and Venable, 1986) and support headteachers' decisions (Mauro, 2007) related to school operational tasks even though they are among the "out-group".…”
Section: Influence Of Lmx Relationship On Teachers' Trustmentioning
confidence: 99%
“…This indicates that teachers are willing to cooperate with their school leaders even though some from the "out-group" have limited relationship with their school leaders. Teachers who show their loyalty to their school headteachers express high commitment and unquestioning faith and trust in their headteachers ( Johnson and Venable, 1986) and support headteachers' decisions (Mauro, 2007) related to school operational tasks even though they are among the "out-group".…”
Section: Influence Of Lmx Relationship On Teachers' Trustmentioning
confidence: 99%
“…Sergiovani (2006) found that interactions among personnel in schools were necessary for promoting and institutionalizing decisions. In addition, a principal's interactive style impact a teachers' construction of others as influential (Cranston, 2001;Johnson & Venable, 1986;Spillane, 2006;Spillane, Hallet, & Diamond, 2003).…”
Section: Controlling 11mentioning
confidence: 99%
“…The 1980s produced a substantial body of general research on how principals influence teachers (Blase, 1987;Blumberg and Greenfield, 1986;Brady, 1985;Bredeson, 1989;Firestone and Wilson, 1985;Hoy and Brown, 1986;Johnston and Venable, 1986). Micropolitical studies, in particular, have been especially important in providing descriptions of how principals influence teachers (Anderson, 1991;Ball, 1987;Blase, 1990).…”
mentioning
confidence: 99%